Green Purchase Intention: An Investigation Green Brand Knowledge and Green Perceived Value of Bioplastic Products in Bandung - Indonesia - Rennyta Yusiana; Arry Widodo; Agus Maolana Hidayat (Research Synergy Foundation, 2021)
Background - Currently, there is environmental and ecosystem damage, one of which is due to the accumulation of waste residue or waste originating from industry and households. Difficult waste to decompose is plastic, they tend to accumulate in landfills, wasted in the sea, and can threaten marine ecosystems. However, if burned will produce substances that are harmful to health. This phenomenon supports people using plastic substitutes, bioplastics. It made from cassava and vegetable derivatives, and environmentally friendly and not harmful if ingested by animals. Purpose – This study aims to determine the effect of Green Brand Knowledge (GBK) and Green Perceived Value (GPV) on Green Purchase Intention (GPI) of bioplastic products in Bandung, Indonesia. Design/methodology/approach – This research is a quantitative research with descriptive and causal data analysis. The number of samples is 100 respondents who use bioplastic products in Bandung-Indonesia. The number of consumers is unknown, so the number of samples is determined by Bernoulli formula. Data collected from the questionnaire, processed using SPSS application and path analysis method. Findings – The results showed that the respondents' perceptions of each variable: Green Brand Knowledge (GBK), Green Perceived Value (GPV) and Green Purchase Intention (GPI) were in the good category. There is a partially significant relationship between Green Brand Knowledge (GBK) and Green Purchase Intention (GPI) and a simultaneous relationship, Green Brand Knowledge (GBK) and Green Perceived Value (GPV) with Green Purchase Intention (GPI) has a very strong and significant relationship. Research limitations – Focusing the dimensions of Green Brand Knowledge (GBK), Green Perceived Value (GPV) and Green Purchase Intention (GPI) to the respondent in Bandung-Indonesia, so the memory in the minds of consumers is centered on these variables. Originality/value – This study provides input on relevant theories regarding the effect of Green Brand Knowledge (GBK) and Green Perceived Value (GPV) on Green Purchase Intention (GPI) of bioplastic products in Bandung-Indonesia and supports increased consumer use of environmentally friendly products. It is known that improvements in the customer dimension and environmental concern are to increase Green Perceived Value (GPV), so that consumers get overall benefits and something is sacrificed based on environmental desires, in the hope that there will be sustainability and an increase in green needs.